The Influence of Flow and Bed Slope on Gas Transfer in Steep Streams and Their Implications for Evasion of CO2. Issue 11 (9th November 2017) - Maurice, L.; Rawlins, B. G.; Farr, G.; Bell, R.; Gooddy, D. C.
Abstract: The evasion of greenhouse gases (including CO2, CH4, and N2 O) from streams and rivers to the atmosphere is an important process in global biogeochemical cycles, but our understanding of gas transfer in steep (>10%) streams, and under varying flows, is limited. We investigated gas transfer using combined tracer injections of SF6 and salt. We used a novel experimental design in which we compared four very steep (18.4–29.4%) and four moderately steep (3.7–7.6%) streams and conducted tests in each stream under low flow conditions and during a high‐discharge event. Most dissolved gas evaded over short distances (~100 and ~200–400 m, respectively), so accurate estimates of evasion fluxes will require sampling of dissolved gases at these scales to account for local sources. We calculated CO2 gas transfer coefficients ( K CO2 ) and found statistically significant differences between larger K CO2 values for steeper (mean 0.465 min −1 ) streams compared to those with shallower slopes (mean 0.109 min −1 ). Variations in flow had an even greater influence. K CO2 was substantially larger under high (mean 0.497 min −1 ) compared to low flow conditions (mean 0.077 min −1 ). We developed a statistical model to predict K CO2 using values of streambed slope × discharge which accounted for 94% of the variation. We show that two models using slope and velocity developed by Raymond et al. (2012) for streams and rivers with shallower slopes also provide reasonable estimates of our CO2 gas transfer velocities ( k CO2 ; m d −1 ). We developed a robust field protocol which could be applied in future studies. Key Points: Gas transfer from steep streams was investigated using tracer tests, with 4 very steep streams compared to 4 moderately steep streams Gas transfer was higher during high flow events, and gas transfer coefficients could be predicted by the product of discharge and slope Most gas evaded within 100 to 400 m highlighting the importance of characterizing gas sources when estimating evasion